Pushing the Limit of the RAFT Process: Multiblock Copolymers by One-Pot Rapid Multiple Chain Extensions at Full Monomer Conversion - Gody, Guillaume; Maschmeyer, Thomas; Zetterlund, Per B; Perrier, Sébastien (Macromolecules, 2014)
We describe an optimized method to prepare multiblock copolymers. The approach is based on our previously reported use of reversible addition–fragmentation chain transfer (RAFT) polymerization, which here has been optimized into a fast, versatile, efficient, and scalable process. The one-pot, multistep sequential polymerization proceeds in water, to quantitative yields (>99%) for each monomer addition, thus circumventing requirements for intermediate purification, in 2 h of polymerization per block. The optimization of the process is initially demonstrated via the synthesis of a model decablock homopolymer (10 blocks) of 4-acryloylmorpholine with an average degree of polymerization of 10 for each block ( Đ = 1.15 and livingness >93% for the final polymer). Both the potential and the limitations of this approach are illustrated by the synthesis of more complex high-order multiblock copolymers: a dodecablock copolymer (12 blocks with 4 different acrylamide monomers) with an average degree of polymerization of 10 for each block and two higher molecular weight pentablock copolymers (5 blocks with 3 different acrylamide monomers) with an average degree of polymerization of 100 per block.